Sinergi Edukasi Literasi Keuangan: Memutus Rantai Korban Investasi Bodong - Rahman Pura; Syamsul Ridjal; Ruslan Ahmad; Nur Syamsu; Rasyid Rahman; Eva Marin Sambo; M. Irwan Nur Hamidin; Jumiati Syam (Lembaga Pengembangan Kinerja Dosen, 2025)
This community engagement program aims to enhance financial literacy as a preventive measure against the widespread issue of fraudulent investment schemes. Titled “Synergy in Financial Literacy Education: Breaking the Chain of Fraudulent Investment Victims”, the activity was conducted in Sanrobone Village and involved 20 participants consisting of local residents and university students. The method employed was an interactive seminar that combined presentations with open discussions. The results showed a significant increase in participants’ understanding of the characteristics of illegal investments, the importance of personal financial management, and the need for caution in making financial decisions. The synergy between academic institutions and the community is expected to serve as a strategic effort to strengthen financial resilience and reduce the number of victims of investment fraud.